Strategi Peningkatan Perekonomian Desa Melalui Ekonomi Kreatif dan Digital Marketing Pada UMKM - Farikha Amilahaq; Ahmad Hijri Alfian; Bahrain Pasha Irawan; Wahyu Agung Rekso; Gielda Ayu Ratu Balqis; Habibah Inas Cahyani; Indharrosa Atina Firdaus; Sofa Nasrul Hidayah (Yayasan Daarul Huda Kruengmane, 2023)
One of the problems that makes the competitiveness of MSMEs is still low is the limited ability of MSME players to carry out marketing and the variety of business products that are not yet balanced with the rapidly changing needs of society. The workshop activities were carried out as part of a service program to provide insight and knowledge for business actors in improving the quality of the village economy in micro, small and medium enterprises (MSMEs) through creative economic opportunities and digital marketing. The method used to provide material from this workshop is carried out offline, followed by intensive assistance with digital marketing and product practices. The implementation of this service program with the theme of creative economy and digital marketing was carried out at the MSME group in Nongkosawit Subdistrict which has a business making various types of chips. The forms of assistance for MSMEs include providing assistance in marketing chips products through marketpalce and social media. From the activities that have been carried out, partners understand enough about the concept of digital marketing and have the ability to use the internet to market these chips. The increased ability of partners in marketing through online media is expected to help partners in obtaining a wider market and increase the competitiveness of partners as MSME actors.